The Importance of Emotional Intelligence for Internal Auditors - Luthfia Osi Dewina (Bappenas Working Papers, 2018)
The purpose of this study is to capture the importance of emotional intelligence for internal auditors in the public sector in Indonesia, considering the advantages of emotional intelligence at the workplace. The research utilizes descriptive survey research as a basis for analysis and found that emotional intelligence was important for internal auditors. Particularly, higher importance was found in conducting consulting activity than assurance services. While communication, trustworthiness, and teamwork and collaboration were the top three most important competencies for internal auditors, empathy was the least crucial one. Furthermore, it was agreed that emotional intelligence was important in ethical behavior, coping stress, communication skill, and professional skepticism.